2013
DOI: 10.1039/c3cc44546a
|View full text |Cite
|
Sign up to set email alerts
|

A dual functional MOF as a luminescent sensor for quantitatively detecting the concentration of nitrobenzene and temperature

Abstract: We report here a luminescent metal-organic framework [Zn3(TDPAT)(H2O)3] [TDPAT = 2,4,6-tris(3,5-dicarboxyl phenylamino)-1,3,5-triazine] exhibiting strong luminescence at room temperature, which can serve as the first case of a dual functional luminescent sensor for quantitatively detecting the concentration of nitrobenzene and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
145
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(150 citation statements)
references
References 61 publications
(1 reference statement)
2
145
0
Order By: Relevance
“…Pioneering work within this field was performed by Li et al who demonstrated the sensitive detection of DMNB and 2,4-DNT in the vapour phase. 37 This work inspired a number of other researchers who subsequently demonstrated the successful detection of explosives, with some selectivity, using zinc, [38][39][40][41][42][43] cadmium, [44][45][46] lithium, 47 indium, 48 europium, [49][50][51][52] and terbium containing metal-organic frameworks. 53 However, the majority of the published research reports the detection of explosives using MOFs through solution-based titrations.…”
Section: −3mentioning
confidence: 89%
“…Pioneering work within this field was performed by Li et al who demonstrated the sensitive detection of DMNB and 2,4-DNT in the vapour phase. 37 This work inspired a number of other researchers who subsequently demonstrated the successful detection of explosives, with some selectivity, using zinc, [38][39][40][41][42][43] cadmium, [44][45][46] lithium, 47 indium, 48 europium, [49][50][51][52] and terbium containing metal-organic frameworks. 53 However, the majority of the published research reports the detection of explosives using MOFs through solution-based titrations.…”
Section: −3mentioning
confidence: 89%
“…Up to now, a few examples in the literature demonstrate this potential application. [15][16][17][18][19][20] On the other hand, organic dyes are one of the major pollutants in water because of their long lifetimes and wide distribution. Recently, numerous methods have been employed for organic dye wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, a large number of luminescent MOF sensors for detecting cations, anions, organic small molecules, explosives and temperature have been realized and reported [6][7][8][9]. Comparing with the traditional luminescent MOFs, the characteristics of the luminescent MOF sensors are the permanent porosity, high surface areas and structural flexibility [10]. Nitrobenzene is notorious environment pollutant, which can cause serious health problems [11].…”
Section: Introductionmentioning
confidence: 99%